2013
DOI: 10.1007/s00436-013-3691-x
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the host spectrum and distribution of Calodium hepaticum (syn. Capillaria hepatica): part 1—Muroidea

Abstract: Calodium hepaticum (syn. Capillaria hepatica) is a worldwide-distributed species of zoonotic nematodes with a high affinity to the liver. Several rodent species of the superfamily Muroidea serve as main hosts for this pathogen. C. hepaticum has been found in Muroidean hosts in more than 60 countries in Europe; North, Central, and South America; Asia; Africa; and Oceania. C. hepaticum was documented in more than 90 Muroidean rodent species (Murinae, Deomyinae, Arvicolinae, Neotominae, Cricetinae, Sigmodontinae,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 73 publications
1
27
0
1
Order By: Relevance
“…La presencia de huevos similares a los de Calodium hepaticum requiere establecer su identidad específica para ser explicada. Calodium hepaticum se ha reportado en todos los continentes y en diversos mamíferos (Fuehrer, 2014) aunque el género Calodium no ha sido reportado en mamíferos actuales de Patagonia (Fugassa, 2015). Contrariamente, huevos similares fueron hallados en numerosos coprolitos de diferentes especies en los sitios arqueológicos de la región (Taglioretti et al 2014).…”
Section: Resultados Y Discusiónunclassified
“…La presencia de huevos similares a los de Calodium hepaticum requiere establecer su identidad específica para ser explicada. Calodium hepaticum se ha reportado en todos los continentes y en diversos mamíferos (Fuehrer, 2014) aunque el género Calodium no ha sido reportado en mamíferos actuales de Patagonia (Fugassa, 2015). Contrariamente, huevos similares fueron hallados en numerosos coprolitos de diferentes especies en los sitios arqueológicos de la región (Taglioretti et al 2014).…”
Section: Resultados Y Discusiónunclassified
“…Rodents are the main host of the roundworm Capillaria hepatica (synonym Calodium hepaticum) and among those, the brown rat has the highest prevalence across the globe [46]. The wide distribution in rats is in line with the geographically widespread human hepatic capillariosis in Europe, although a rarely reported disease [47].…”
Section: Geographical Distribution Of Rat-borne Pathogens Within Europementioning
confidence: 99%
“…Waugh et al [14] reported on the zoonotic potential of helminths of R. rattus and Rattus norvegicus from Jamaica, recording the presence of six nematodes, two cestodes and an acanthocephalan. Fuehrer [15] reported the occurrence of Capillaria and Hymenolepis in wild rats in the United Kingdom, while d'Ovidio et al [16] and Garedaghi and Khaki [17] also reported on the presence of Hymenolepis diminuta in gray squirrel from Indiana and Hymenolepis species in captured rodents in Iran, respectively.…”
Section: Discussionmentioning
confidence: 99%